Predicting Model of Density for Crude Oil Blends at (Al-Wafa& Al-Feal)Field of Mellita Compound-Libya - Allali Khalid. Hamid (Aljameai, 2023)
a bstract:Density is considerable importance trait for evaluating transfer and treatment  properties in crude oils  processing. Information about  density plays a very important role to a solve engineering problems concern  fluid flow phenomena and momentum transfer. In the current study, Five were prepared with different sample crude  oils  blends from a very light crude oil Al-Wafa (W)  and a light crude oil Al-Feal (F)  as follows: Blend1 (20%W , 80% F ); Blend2 (35% W , 65% F ) ; Blend3 (55% W , 45% F ); Blend4 (70% W , 30% F) and Blend5 (85% W , 15% F) at different temperatures (20, 25, and 30 °C) to obtain the experimental density; to develop the reliable mathematical expression for the most important physical properties using non-linear regression and to analyze the predictive model results using standard statistical techniques. The predicted density results have been validated with the experimental density data gathered in the laboratory. High precision results between the predicted and experimental values have been noticed  with overall average absolute deviation (AAD %) of 0.48%.  From the predicted results in this study , it can be concluded that the performance of the developed model are excellent.المستخلص: تعتبر الكثافة خاصية ذات أهمية كبيرة لتقييم الخصائص الانتقالية في عمليات نقل و معالجة النفط الخام . ومعرفة المعلومات حول الكثافة يلعب دورا مهماً جداً في حل المشاكل الهندسية المتعلقة  بتدفق السوائل وانتقال الزخم . و في الدراسة الحالية ,  تم تحضير خمسة عينات مختلفة الزيت الخام الممزوجة  من زيت خام الوفاء الخفيف جداً  (W)و زيت خام الفيــل الخفيـــف  (F)وكانت على النحو التالـي  -:خليـط 1 ; ( F% 80 ,W% 20) خليط 2 ( 35 % W , 65 %F ) ; خليط 3 (55 %  ,W45 % F) ; خليـط 4 (70% ,W30%F) ;  خليط 5 (85 %  ,W15% F ) عند درجة حرارة (20°C 30, 25, ) للحصول على الكثافة التجريبية ؛ ومن تم تطوير صيغة  رياضية يمكن الاعتماد عليها للتنبؤ بالخصائص الفيزيائية ودلك باستخدام طرق الانحدار غير الخطية ، وتحليل نتائج النموذج المتحصل عليها  باستخدام الطرق الإحصائية القياسية. وقد تم التحقق من صحة النتائج المتوقعة  لقيم الكثافة بمقارنتها مع البيانات التجريبية التي تم قياسها في المختبر . ولوحظت نتائج عالية الدقة  بين القيم المتوقعة والتجريبية  بمتوسط  ​​الانحراف  المطلق  الكلي    (% AAD) حوالي (%0.48).  ومن النتائج المتوقعة في هذه الدراسة,  يمكن الاستنتاج أن أداء النموذج المطور كان ممتازًا.